Formulasi Strategi Pengembangan Usaha Cafe: Formulation of Business Development Strategies in Cafe - Fina Windayani; Popong Nurhayati; Sufrin Hannan (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: The rise of coffee shops in Bogor City is increasing every year. In the middle of a tightly populated café industry with coffee commodities, business actors are still recovering due to the impact of COVID-19.Purpose: This study aims to analyze the internal using the VRIO analysis method through a resource-based view (RBV) approach and external factors using the Porter's Five-Forces approach a PEST Analysis (politic, economy, social, and technology) of The Coffee Companion in facing competition, formulate suitable strategies, and determine priority strategies that can be implemented by the company. Design/methodology/approach: The analytical tools for this research include; the IFE matrix, EFE matrix, VRIO, PEST, and QSPM.Findings/Result: The results of the IE matrix analysis show alternative strategies that can be execute; intensive strategies (market penetration, market development, and product development) or integrative (backward integration, forward integration, and horizontal integration). There are four alternative strategies; improving the quality of existing products, increasing supplier control, improving marketing strategies, and expanding product distribution channels. The results of the QSPM analysis show that the best alternative strategy is to improve the quality of existing products which is 6.57 greater than the other three alternative strategies.Conclusion: The main strategy suggested to companies is to improve the quality of existing products. Followed by increasing control over suppliers, improving marketing strategies, and expanding distribution channels.Originality/value (State of the art): In implementing strategies that have been formulated by adapting to current conditions and making improvements to financial conditions and managing capabilities in facing changing consumer trends. Keywords: PEST analysis, RBV, strategy formulation, VRIO